If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = x + -8 Reorder the terms: 1 + 2x = x + -8 Reorder the terms: 1 + 2x = -8 + x Solving 1 + 2x = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + 2x + -1x = -8 + x + -1x Combine like terms: 2x + -1x = 1x 1 + 1x = -8 + x + -1x Combine like terms: x + -1x = 0 1 + 1x = -8 + 0 1 + 1x = -8 Add '-1' to each side of the equation. 1 + -1 + 1x = -8 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = -8 + -1 1x = -8 + -1 Combine like terms: -8 + -1 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| -1.5a+1+3.5=1.875 | | 3(w-10)+4(w-19)=13 | | -6x-3x=-5x+0 | | -x+15=x+3 | | 4.7y=14.1 | | 4n+7=2 | | 3x^2-4=-79 | | 2x^2-20x=0 | | 2x+17=x+8 | | (7x-1)=3(2x+1)-4(x+6) | | 18s-13=4s-1 | | -0.5x-1.7=0.3x-1 | | 350+25h=67+25h | | 7(y-7)=10(2y-4) | | 35-4(5x-7)=(-20) | | 4x^2+8=264 | | x-2=2x+4 | | 5z-8-z+4=0 | | 1.50x=-7 | | 25w^2-60wf+36f^2=0 | | 3x+13=x+5 | | 6x-7=-47 | | 19a-3a(a-6)=66 | | -81=7+8x | | 0.23x+0.48(60-x)=0.33(60) | | 7lnx=11 | | h(3)=3/3 | | 2x^2-2x+13=0 | | 8x^2-10x+7=0 | | -8-8(1-r)= | | 13x-7+3x-3=12x-4+3x | | 8+0.25c=-6 |